Intelligent Gameplay for Improved Retro Games - Losanie Ravi, Puvana; Ruhaiyem, Nur Intan Raihana (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
In the wake of increasing nostalgia and the success of retro-compilations in the sixth and seventh generations of consoles, ‘retro gaming’ has become a motive in modern games, as well. The goal of this project is to remake and improve a classic puzzle game with intelligence gameplay element and better graphics for Android users namely “Coins Wipeout”. The development of the gameplay intelligence will involve the use of a game engine – where three game mode are introduced; “Qualifier”, “Knockout” and “Wipeout”. The success of the project will surely contribute in success of retro games industry